i'm just not seeing it for these: ln(e^(e^(x)) and ln(e^(2lnx) i don't know where to begin! and is this one correct ln(e^secx)= ln(e)^secx= secxlne=secx
Follow Math Help Forum on Facebook and Google+
Originally Posted by genlovesmusic09 i'm just not seeing it for these: ln(e^(e^(x)) = e^x and ln(e^(2lnx) = ln x^2 i don't know where to begin! and is this one correct ln(e^secx)= secx ln and e are inverses so they reduce y=x. Does this make sense? Ienteredthe right answers in for you
Last edited by 11rdc11; Sep 8th 2009 at 09:47 PM.
Hello genlovesmusic09 Originally Posted by genlovesmusic09 i'm just not seeing it for these: ln(e^(e^(x)) and ln(e^(2lnx) i don't know where to begin! and is this one correct ln(e^secx)= ln(e)^secx= secxlne=secx Two of the basic properties of logarithms (to any base, ) are: , and in particular, So, if we apply these to your two questions: and , which you can write as if you like (again using the first of these laws). Grandad
View Tag Cloud